Formative assessment in times of COVID-19: the perception of the university students - Montes-Iturrizaga, Iván (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Within the framework of COVID-19, there was an abrupt transition from face-to-face to virtual mode in Peruvian universities. This would have triggered a series of challenges and tensions in pedagogical practices. Thus, this research analyses evaluative practices from the perspective of students (n = 194) at a university in Lima. A descriptive (quantitative) comparative and correlational (quantitative) study was chosen. The results suggest that the formative assessment of learning has experienced a clear decline, given the excessive use of tests that select answers and to the detriment of those that explore performance.